Gene synthesis allows biologists to source genes from farther away in the tree of life - Aditya M. Kunjapur (Nature Portfolio, 2018)
Gene synthesis has expanded the ability to modify and create DNA sequences, with implications for biosurveillance. The authors use machine learning and codon theory to identify synthetic genes in Addgene data, and show that synthesis accelerates human-directed gene transfer across the tree of life.